A Theoretical Study of the Diels-Alder Reaction between 3-nitrofuran and Different Dienes Developed in Ionic Liquids - Cainelli, Mauro (2016)
In this study the reactivity of 3-nitrofuran acting as electrophile in their reactions with different dienes, was analyzed in theoretical form. Specifically, the mechanism of each DA reaction was explored. Moreover, considering the polar character of this type of cycloaddition reaction we have discussed the modification of the dienophile reactivity when the solvent effect is considered by adding molecules of ILs to the dienophile optimizations.